Analisis Perbandingan Implementasi Clean Architecture Menggunakan MVP, MVI, Dan MVVM Pada Pengembangan Aplikasi Android Native - Firmansyah Firdaus Anhar; Made Hanindia Prami Swari; Firza Prima Aditiawan (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
Clean architecture is a method of application development that divides code into multiple layers based on the purpose of the code, ensuring minimal dependency. Popular architectures in Android application development include MVP (Model View Presenter), MVI (Model View Intent), and MVVM (Model View ViewModel). This research focuses on creating three applications with similar features and interfaces using different architectures. The study compares modifiability, testability, and performance aspects to determine the differences between each architecture. The results show that MVVM architecture is the best in modifiability, with the lowest number of index modifications. Testability requires no more than four scenarios for all architectures. However, MVI architecture outperforms in test coverage, and MVP architecture outperforms in performance. Overall, clean architecture is a valuable approach for improving the performance and usability of Android applications.